Placing health : neighbourhood renewal, health improvement, and complexity - Blackman, Tim (Policy, 2006)
Where people live matters to their health. Health improvement strategies often target where people live, but do they work? Placing Health tackles this question by exploring new theoretical, empirical and practice perspectives on this issue, anchored by major studies of England's Neighbourhood Renewal Strategy and the Programme for Action on health inequalities.